The icaA gene in staphylococci from bovine mastitis - Rumi, María Valeria; Huguet, Miguel J; Bentancor, Adriana B; Gentilini, Elida R (The Journal of Infection in Developing Countries, 2013)
Introduction: Staphylococcus aureus and coagulase-negative staphylococci (CNS) are frequently isolated from cows with mastitis. A main virulence factor of CNS is the ability to adhere and form biofilms. The intercellular gene cluster adhesion (ica) operon is one factor involved in biofilm production although ica-independent factors are also involved. Previous reports based on the results of S. epidermidis and S. aureus suggested that ica is highly conserved between species, but this detection decreases in other CNS biofilm producers. In this study we evaluated the presence of the icaA gene in strains of Staphylococcus spp. isolated from the milk of bovines with mastitis. Methodology: Thirty-seven staphylococci strains were evaluated by detecting the icaA gene. A new set of PCR primers was designed by consensus region of eight staphylococci from GenBank. Species characterization was performed using the Kloos and Schleifer scheme. Results: We identified the presence of the gene in S. aureus (n:4), S. chromogenes (n:4), and S. sciuri strains (n:2). We also, identified the presence of the gene in S. xylosus (n:5) for the first time. The icaA gene was not detected in S. capitis (n:1), S. epidermidis (n:2), S. hominis (n:2), S. saccharolyticus (n:1), S. simulans (n:4) and S. saprophyticus (n:3). The icaA gene was detected in 40.54% (15/37) of the CNS evaluated. Conclusions: Our results confirm the presence of the ica operon in various species of CNS pointing to polysaccharide intercellular adhesin (PIA) as the most important component for the formation of biofilms.